2012
DOI: 10.1200/jco.2011.39.3652
|View full text |Cite
|
Sign up to set email alerts
|

Use of Tanning Beds and Incidence of Skin Cancer

Abstract: PurposeWe sought to evaluate the risk effect of tanning bed use on skin cancers among teenage and young adults. We also expected to determine whether a dose-response relationship was evident.Patients and MethodsWe observed 73,494 female nurses for 20 years (from 1989 to 2009) in a large and well-characterized cohort in the United States and investigated whether frequency of tanning bed use during high scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
152
1
9

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(169 citation statements)
references
References 42 publications
7
152
1
9
Order By: Relevance
“…Ultraviolet (UV) exposure is the primary and preventable risk factor for skin cancer [12][13][14]. Indoor UV tanning appears responsible for part of the rise over the past several decades among young women [15,16]. More frequent use, use of higher intensity devices, and use over longer periods of time have all been linked to elevated melanoma risk [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultraviolet (UV) exposure is the primary and preventable risk factor for skin cancer [12][13][14]. Indoor UV tanning appears responsible for part of the rise over the past several decades among young women [15,16]. More frequent use, use of higher intensity devices, and use over longer periods of time have all been linked to elevated melanoma risk [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Indoor UV tanning appears responsible for part of the rise over the past several decades among young women [15,16]. More frequent use, use of higher intensity devices, and use over longer periods of time have all been linked to elevated melanoma risk [15,16].The annual prevalence of indoor tanning in the USA is highest among non-Hispanic white women between the ages of 18-21 (32 %) and 22-25 (30 %) [17]. Two thirds (68 %) of 18-21-year-old non-Hispanic white women who use indoor tanning report frequent use (10 or more indoor tanning sessions per year), with an average of nearly 28 indoor tanning sessions per year [17].…”
mentioning
confidence: 99%
“…In this study, number of times per year participants reported using a tanning bed was associated with risk of BCC, particularly among those who used tanning beds at a younger age, such as during high school or college; the relative risk for 4 times per year compared with no use in high school or college was 1.40, and for 25 to 35 years of age it was 1.19. 21 However, this report did not specifically evaluate earlyonset tumors. Likewise, in our previous report, based on only the first phase of accrual, 25 we were unable to examine risk of developing an early-onset tumor or the impacts of early age at exposure in much detail because of the limited sample size.…”
Section: Discussionmentioning
confidence: 99%
“…14,[16][17][18][19] Previous studies provide consistent evidence about the risks of melanoma and squamous cell carcinomas of the skin related to tanning lamp use. 15,20,21 More recent work raises the possibility of an elevated risk of BCC from early exposure, 21,22 and that exposure may lead to earlier onset of the disease. 23 As part of a population-based case-control study of BCC, we had an opportunity to examine age at first tanning lamp exposure in relation to the incidence of early-onset BCC and to investigate whether effects were specific to the type of device used (eg, sunlamps, tanning beds, or booths) or period of use.…”
mentioning
confidence: 99%
“…6 "Ever use" of tanning beds before the age of 25 was found to significantly increase melanoma risk, [8][9] and correlations have also been found between indoor tanning and basal and squamous cell carcinoma. [9][10][11] The National Sun Survey II 1 (NSS2) estimated that 10.5% of the Canadians surveyed in 2006 tanned indoors in the past year, an increase from 7.7% in 1996, which suggests a growth in popularity. The NSS2 also found that indoor tanning is more common among females, particularly young women, a finding echoed by research conducted elsewhere.…”
Section: Introductionmentioning
confidence: 99%